Technological processes study for high value health ingredients and foods production - Bonoli, Matteo <1978> (Alma Mater Studiorum - Università di Bologna, 2008)
This PhD thesis describes set up of technological models for obtaining high health value foods and ingredients that preserve the final product characteristics as well as enrich with nutritional components. In particular, the main object of my research has been Virgin Olive Oil (VOO) and its important antioxidant compounds which differentiate it from all other vegetables oils. It is well known how the qualitative and quantitative presence of phenolic molecules extracted from olives during oil production is fundamental for its oxidative and nutritional quality. For this purpose, agronomic and technological conditions of its production have been investigated. It has also been examined how this fraction can be better preserved during storage. Moreover, its relation with VOO sensorial characteristics and its interaction with a protein in emulsion foods have also been studied. Finally, an experimental work was carried out to determine the antioxidative and heat resistance properties of a new antioxidant (EVS-OL) when used for high temperature frying such as is typically employed for the preparation of french fries. Results of the scientific research have been submitted for a publication and some data has already been published in national and international scientific journals.